The development of a measurement system for water-energy-food (WEF) security Nexus in Malaysia: wellbeing, sectoral balance and sustainable development - Tan, Andrew Huey Ping (2018)
It is undeniable that activities and events within the water, energy, and food (WEF) security nexus are inextricably linked and their relationships numerous and substantial. Complexity increases when factors governing the daily lives of humanity namely social, technology advancement, environment, economic, and policies (STEEP) adds upon the difficulty in addressing the relationships. It is thus paramount to address the problems from a holistic and systematic approach to maximise benefits as well as to minimize the negative impacts upon one another. However, there exists little to zero means of measuring their performance, whether qualitatively or quantitatively, within the context of a nexus. Moreover, minimal understanding exists regarding the relationships between the WEF securities in Malaysia, an emerging economy rich in natural resources, which envisions to be a developed nation. This research sought to establish a measurement system for the WEF security nexus in Malaysia within the context of resource security wellbeing, sectoral balance, and sustainable development using a System Dynamics (SD) approach. This entailed an extensive literature review and qualitative interview with key stakeholders from the industrial sectors. The front end of the SD process is concerned with obtaining important and relevant information from literature and interviews, which are then used to construct causal loop diagrams (CLD). The back end of the SD is concerned with converting the CLDs into a stock and flow diagram (SFD), which provides a platform for quantitative simulation of different well-designed scenarios. Key findings from this research can be highlighted; these include: renewables are necessary for the long-term energy plan of Malaysia, nuclear power is necessary to keep electricity tariff low, water tariff of supply and services are severely low, increasing self-sufficiency level (SSL) of Malaysia’s staple food is important, under-utilised crops are efficient in meeting nutrient requirements, and cash crops imposed systemic stresses upon the water sector more than the energy sector. Consequently, recommendations for policy makers are suggested accordingly to achieve a reasonable proportion of RE penetration, providing education on nuclear benefits, centralising and streamlining water governance, socio-economic improvement of water economics, increase SSL of staple food, embark upon widespread adoption of local under-utilized crops, and controlling land use of non-food crops. The outcome of this research forms a vital and novel contribution to knowledge, when it is a pioneering work to address the WEF security nexus for Malaysia; especially in considering their securities for the country as a system rather than unaffected individual entities. This work will contribute towards spearheading the awareness and, hopefully, trigger further and more in-depth work in transdisciplinary resource and technology management. As a pioneering effort, this research has nonetheless provided the foundation and the fundamental understanding to an integrative and inclusive cross-sectoral national resource backbone - The WEF security nexus measurement system of Malaysia.